Particle scale study on the crystallization of mono-sized cylindrical particles subject to vibration - Qian, Quan; An, Xizhong; Zhao, Haiyang; Dong, Kejun; Wu, Yongli; Fu, Haitao; Zhang, Hao; Yang, Xiaohong (Powder technology, 2019)
In this paper, the transition from random to ordered packings of mono-sized cylindrical particles under 3D mechanical vibration was simulated by discrete element method (DEM). The effects of particle aspect ratio, size of the particulate system and container wall on the granular crystallization were investigated. And the mechanisms were analyzed through the characterization of the order transition process in terms of packing density, coordination number (CN), orientational ordering parameter (O), nucleation and growth of cluster and granular temperature (θ). The results show that nearly perfect crystallization of mono-sized cylindrical particles can be achieved with specific aspect ratio and proper vibration conditions in a cylindrical container. The orientational ordering parameter demonstrates that the crystallization firstly starts from the container wall and then propagates inward gradually. The lower granular temperature in a cuboid container indicates less vibration energy transferred to the granular assembly compared with that in a cylindrical container, illustrating the critical role of container shape in crystallization. The vibrated crystallization of mono-sized cylindrical particles is analogous to entropy-driven process, which can be gradually achieved by the self-assembly of particles with parallel alignments along the already formed ordered clusters (nuclei) or the container wall. These results can help design complex and ordered granular structures. [Display omitted] •Vibrated packing ordering of mono-sized cylindrical particles is simulated by DEM.•Effects of different factors on the packing ordering (crystallization) are analyzed.•Various macro/micro properties during crystallization are characterized.•Crystallization dynamics and mechanism are investigated.